Effect of essential oil on hypertrophic scars - Rahman, Ave Olivia; Humaryanto, Humaryanto; Purwakanthi, Anati; Simanjuntak, Charles Apul (Universitas Muhammadiyah Purwokerto, 2021)
Background: Hypertrophic scars are abnormal scars resulted from a disrupted wound healing process. Hypertrophic scars can affect the body aesthetic of the sufferers, but, on the other hand, conventional therapy has not been optimally effective. The application of essential oil combinations as an alternative therapy for hypertrophic scars has not been scientifically proven.Purposes: This study was to determine the effectiveness of the essential oil as a hypertrophic scar therapy.Methods: This study used a pre and post-test design. As many as 24 subjects aged 17-25 years with hypertrophic scars were given essential oil combinations every morning and evening for six months. Assessment of hypertrophic scars was done using the POSAS (Patient and Observer Scar Assessment Scale).Results: The results showed that the POSAS score decreased after the essential oil combination administration for six months, 14.40±6.08 vs. 22.67±8.31 (p<0.001).Conclusion: the combination of essential oil oils used in this study reduces hypertrophic scars based on the POSAS assessment.